Psychiatric risk factors in Formula One and the importance of integrating mental health into driver science - Colangelo, Jill; Smith, Alexander; Keay, Nicky; Buadze, Ana; Liebrenz, Michael (Frontiers in Sports and Active Living, 2024)
Formula One (F1) racing has recently grown in popularity, extending well beyond its traditional European roots. However, there has been a paucity of scholarly research dedicated to the health of drivers and even less discussion of the prevalence of psychiatric symptoms, risk factors, and types of psychopathology in F1. This is notable given advancements in sports psychiatry and evidence of psychiatric disorders emerging across other sports. Accordingly, this perspective paper details the physiological conditions in F1 and the socioenvironmental pressures that a driver may encounter during their career, including heat stress, weight restrictions, harassment, and other factors. These extreme physiological and psychological stressors, both in racing and non-racing environments, alongside sport-specific psychosocial pressures, may cause HPA axis dysregulation and other issues in drivers, heightening vulnerabilities for mental health concerns. Additionally, F1 is still affected by stigmatizing attitudes and regressive sociocultural norms, which could inhibit progress toward promoting sustainable wellbeing. Consequently, drivers may be at risk for mental disorder and a decrease in overall health and wellbeing. Against this background, we thereby recommend mental health programs and regulatory actions that could better address these challenges and promote mental wellbeing across F1.